Efektivitas Air Rendaman Jerami Alang-Alang (Imperata cylindrica) sebagai Atraktan terhadap Jumlah Telur Aedes aegypti - Budi Hairani; Muhammad Rasyid Ridha; Abdullah Fadilly; Gusti Meliyanie; Akhmad Rosanji (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2020)
The use of ovitrap with attractants modification has been known as an alternative method in controlling DHF vectors. Attractant material will be better if it uses natural ingredients that are cheap and easy to obtain and easy to manufacture. Attractant material is recommended to use natural ingredients that are cheap and easy to obtain and are easy to make. Imperata plants can be easily obtained and easily processed as attractant material. This study aims to determine the effectiveness of attractants on a laboratory scale in the form of immersion water from the straw of the Imperata cylindrica plants in various concentration levels to Aedes aegypti eggs number. Research with an experimental design using a completely Randomized Design (CRD) was conducted at the Entomology Laboratory of the Tanah Bumbu Research and Development Center, in July 2019. Treatment concentrations consisted of 5%, 10%, 15%, and 20%, control using akuades. Samples for testing using Ae. aegypti gravid mosquitoes. Treatment with 5 repetitions, carried out for 7 days. Data analyzed by normality test, Anova test, and Least Significant Differences (LSD) test. The average number of eggs at concentrations of 5%, 10%, 15%, and 20% respectively was 45.00; 78.60; 129.40; and 174.00. Anova test showed Imperata cylindrica straw soaking attractant had a significant effect on oviposition of Ae. aegypti mosquitoes. LSD test results showed attractant 15% is the optimal concentration in increasing the number of eggs in the ovitrap.